Pengembangan LKPD Berbasis Wayground Bermuatan Kearifan Lokal dalam Pembelajaran Membaca Teks Puisi Kelas XI di SMA Negeri 1 Gamping - Desvina Rahmadani; Nina Widyaningsih (Universitas Wijaya Kusuma Surabaya, 2026)
This study aimed to develop a Waygroundbased Student Worksheet (LKPD) integrated with local wisdom for teaching poetry reading to eleventh grade students by employing the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). The results of the media expert validation showed a score of 90,67%, categorized as excellent; the material expert validation reached 96.00%, categorized as excellent; and the assessment expert validation obtained 89,17%, also categorized as excellent. Based on students’ responses, the product achieved 94,33% in the smallgroup trial and 92% in the largegroup trial, while the teacher’s response reached 90%. Furthermore, the average pretest score was 58,5183, whereas the average posttest score increased to 81,1106. The normality test indicated that both pretest and posttest data were normally distributed. Subsequently, the paired samples t-test produced a significance value of 0.000 < 0,05, indicating that the LKPD had a significant effect on improving students’ learning outcomes. In addition, the N-Gain result was 0,5927, with a percentage of 59,2705%, which falls into the moderately effective category. Therefore, the Wayground-based LKPD integrated with local wisdom is considered feasible, attractive, and moderately effective for use in teaching poetry reading.